2021
DOI: 10.1016/j.amsu.2021.102420
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific implants for craniomaxillofacial surgery: A manufacturer's experience

Abstract: Additive manufacturing technologies have enabled the development of customised implants for craniomaxillofacial applications using biomaterials such as polymethylmethacrylate (PMMA), porous high-density polyethylene (pHDPE), and titanium mesh. This study aims to report an Australian manufacturer's experience in developing, designing and supplying patient-specific craniomaxillofacial implants over 23 years and summarise feedback received from clinicians. The authors conducted a retrospective review of the manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…They are classified based on the materials used, such as polymethylmethacrylate (PMMA), porous highdensity polyethylene (pHDPE), and titanium mesh. Previous studies have demonstrated their clinical and surgical efficacy [6]. This case report presents the clinical presentation of a 22-year-old female patient with a mural-type unicystic ameloblastoma situated in the posterior region of the left mandible.…”
Section: Introductionmentioning
confidence: 91%
“…They are classified based on the materials used, such as polymethylmethacrylate (PMMA), porous highdensity polyethylene (pHDPE), and titanium mesh. Previous studies have demonstrated their clinical and surgical efficacy [6]. This case report presents the clinical presentation of a 22-year-old female patient with a mural-type unicystic ameloblastoma situated in the posterior region of the left mandible.…”
Section: Introductionmentioning
confidence: 91%
“…The synthetic polymers polyether ether ketone (PEEK), poly­(methyl methacrylate) (PMMA), and porous high-density polyethylene (pHDPE) have been widely used to treat large cranial defects, specifically for brain protection and shape restoration instead of promoting bone regeneration because they are osteoconductive but not osteoinductive . Other synthetic polymers tested to a lesser extent in vivo are the nonresorbable and cytocompatible material polystyrene (PS), and poly­(ethylene- co -vinyl alcohol)/poly­(δ-valerolactone) (PEVAV) .…”
Section: Biomaterials Employed To Fabricate Scaffolds Suitable For Cm...mentioning
confidence: 99%
“…Additionally, surface modifications have conferred osteoinductivity and have reduced metal ion release improving their biocompatibility . Nowadays, titanium meshes are frequently placed and fixed with screws around grafted materials in CSDs, peri-implant defects, and alveolar ridge augmentations. , …”
Section: Biomaterials Employed To Fabricate Scaffolds Suitable For Cm...mentioning
confidence: 99%
“…The "ideal" BTE scaffold should also modulate cellular interactions, promote vascularisation, and replicate the mechanical properties at the target site [5,6]. Additionally, the preparation and sterilisation techniques need to comply with industry and regulatory standards [7]. To this end, this review explores the structure and function of bone, as well as the current strategies used to treat defects.…”
Section: Introductionmentioning
confidence: 99%